Growth components and gas exchange in Tecoma stans L. plants under water stress - Alves, Magnólia; Albuquerque, Manoel Bandeira de; Pedroza Cruz , Renata Ranielly; Jardelino Dias , Thiago; de Medeiros, Eliane Cecília (Comunicata Scientiae, 2025)
The reduction in water availability has significant effects on plant physiology and morphology, leading to changes in metabolism that impair the plant establishment in the field. This study aimed to evaluate the effects of water stress on morphophysiological traits of Tecoma stans (L.) Juss. ex Kunth seedlings. The experimental design was conducted in a completely randomized design, with four irrigation intervals: daily irrigation (control), and irrigation intervals of 5, 10, and 15 days. Plant height and leaf number were measured weekly after the 15th day after transplanting and the root length, dry matter, and biomass allocation in different plant organs were determined after 60 days. Gas exchange measurements were also assessed. Tecoma stans showed significant response to water stress due to the extended irrigation intervals, showing a significant reduction in plant height, leaf number, dry matter (stem, leaves, roots, and total dry matter). Photosynthetic rates ranged from 1.8 μmol m⁻² s⁻¹ under the longest irrigation interval to 13.6 μmol m⁻² s⁻¹ in plants irrigated daily, with transpiration rates following a similar behavior. The highest gas exchange rates were observed under daily irrigation. The most significant negative effects on photosynthesis, transpiration, and particularly stomatal conductance were observed in plants irrigated under intervals of 10 and 15 days.